Analyzing Multilingual French and Russian Text using NLTK, spaCy, and Stanza - Goodale, Ian (The programming historian, 2024)
This lesson covers tokenization, part-of-speech tagging, and lemmatization, as well as automatic language detection, for non-English and multilingual text. You’ll learn how to use the Python packages NLTK, spaCy, and Stanza to analyze a multilingual Russian and French text.